Toward Sustainability: Understanding the Impact of Economic Growth, Urbanization, Energy Use, and Resource Management on Carbon Emissions - Khan, Uzma; Khan, Aarif Mohammad; Alam, Md Shabbir; Houaneb, Amira (International Journal of Energy Economics and Policy, 2025)
This research explores the interconnectedness of sustainability and the effects of economic growth, urbanization, energy use, and resource management on carbon emissions. Despite its importance, there has been limited investigation into this nexus, particularly leveraging advanced statistical methods. We employed several econometric methodologies, including Granger’s causality test, to assess the direction of causation. The ARDL bounds test reveals a significant long-term relationship, with an adjustment speed towards equilibrium of 37 percent. Analysis indicates that a 1% increase in energy consumption is associated with a 0.98% rise in carbon emissions. The findings imply that carbon emissions play a role in economic growth, highlighting a relationship between Kuwait’s energy consumption and tourism. Moreover, urbanization is linked to increased energy consumption, carbon emissions, and economic development. The growth of the economy and rising energy use may indirectly foster tourism. Kuwait can navigate a more sustainable and resilient future amidst global climate challenges by understanding and addressing the complex challenges of tourism, energy consumption, urbanization, and economic growth. This study aims to assist policymakers and researchers in developing more effective environmental and energy policies to reduce carbon dioxide emissions in particular and neighbouring countries.